Pengaruh Aplikasi Eco-enzyme Untuk Menekan Penyakit Moler Pada Tanaman Bawang Merah (Allium ascalonicum L.) Di Lahan Gambut - Alwina Ayu Anggita; Salamiah Salamiah; Helda Orbani Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
This research aims to determine the effect of eco-enzyme application in suppressing moler disease in shallot plants (Allium ascalonicum L.) in peatlands. This research used the Completely Randomized Design (CRD) method, where the treatments used in this study consisted of 4 treatments, namely control (without eco-enzyme solution) and 3 treatments of eco-enzyme solution with doses (0.2, 0.6, and 1 mL/200 mL water) which is repeated 5 times. The results of the research showed that the percentage of eco-enzyme that was able to suppress moler disease in treatment t3 (dose 1 mL/200 mL water) was 57.9%, and the smallest percentage of suppression in treatment t1 (dose 0.2 mL/200 mL water) was 43 .6%. In the incubation period research, Fusarium oxysporum appeared for the first time on the 14th day of DAP and occurred in all treatments. Meanwhile, the highest number of tubers/ha was in the control treatment at 58.40 tubers/treatment (162,222 tubers/ha). In the study, the wet weight of tubers in the control treatment had the heaviest tuber wet weight, namely 522.60 tubers/treatment (1,451.7 kg/ha), and the largest tuber diameter was in the treatment given eco-enzyme solution at a dose of 0.6 mL/200 kg. mL of water is 18.3 mm.